Notes on Early Land Plants Today - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2012)
The adoption of the Global Strategy for Plant Conservation (GSPC) as part of the Convention on Biological Diversity (CBD) has reinforced the urgent need for a global plant checklist to support, facilitate and monitor the conservation and sustainable use of plant diversity worldwide (Lughadha 2004). Without this list many of the other objectives in the GSPC cannot be met, and more broadly, in botanical science as a whole, our ability to communicate about plants on a global basis will be compromised (Crane 2004). The Early Land Plants Today project (see http://www.elpt.org) is a multi-institutional and multi-national endeavour preparing a working checklist for liverworts and hornworts worldwide (von Konrat et al. 2010).